Simulation of airbag impact on eyes with different axial lengths after transsclerally fixated posterior chamber intraocular lens by using finite element analysis - Huang J (Dove Medical Press, 2015)
Jane Huang,1 Eiichi Uchio,1 Satoru Goto2 1Department of Ophthalmology, Fukuoka University School of Medicine, Fukuoka, 2Nihon ESI KK Technical Division, Tokyo, Japan Purpose: To determine the biomechanical response of an impacting airbag on eyes with different axial lengths with transsclerally fixated posterior chamber intraocular lens (PC IOL).Materials and methods: Simulations in a model human eye were performed with a computer using a finite element analysis program created by Nihon, ESI Group. The airbag was set to be deployed at five different velocities and to impact on eyes with three different axial lengths. These eyes were set to have transsclerally fixated PC IOL by a 10-0 polypropylene possessing a tensile force limit of 0.16 N according to the United States Pharmacopeia XXII.Results: The corneoscleral opening was observed at a speed of 40 m/second or more in all model eyes. Eyes with the longest axial length of 25.85 mm had the greatest extent of deformity at any given impact velocity. The impact force exceeded the tensile force of 10-0 polypropylene at an impact velocity of 60 m/second in all eyes, causing breakage of the suture. Conclusion: Eyes with transsclerally fixated PC IOL could rupture from airbag impact at high velocities. Eyes with long axial lengths experienced a greater deformity upon airbag impact due to a thinner eye wall. Further basic research on the biomechanical response for assessing eye injuries could help in developing a better airbag and in the further understanding of ocular traumas. Keywords: airbag, ocular trauma, computer simulation, transsclerally fixated posterior chamber intraocular lens, finite element analysis